Analysis of problems of storage and processing of data in serverless technologies - Naumenko, Tetiana; Petrenko, Anatolii (Technology audit and production reserves, 2021)
The object of research is the problems of storing and processing data in serverless technologies. The research carried out is based on a logical approach to storage, data processing and transmission processes. The main hypothesis of the study is that when moving from a monolithic architecture to microservice architecture, and then from a microservice architecture to a serverless architecture, the process of storing and processing data requires modifications and new approaches to solving classical problems of working with data. The problem of interacting with data is an integral part of the work of almost all computer systems, as they lay the basis for the goal of creating such systems. Serverless computing has already taken root in cloud computing. Improving its work is now one of the most popular tasks in the research field. In this article, let’s review one of the global problems – integrating serverless computing system with a database. As well as currently existing partial or complete solutions. Progress in this area can give impetus to the development of serverless technologies that supplant more outdated software development approaches. The result of these studies brings a certain understanding at what stage of development the above question is now. It also describes the advantages and disadvantages of the new systems. It is considered what innovations have been brought by the global giants in the development of serverless platforms, and what solutions are applied to open source platforms. This issue has not been fully resolved and requires developments and improvements, and therefore remains an excellent direction for development and new research.